2022
DOI: 10.48550/arxiv.2201.01788
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Robust Description of Hadronic Decays in Light Vector Mediator Models

Ana Luisa Foguel,
Peter Reimitz,
Renata Zukanovich Funchal

Abstract: Abelian U (1) gauge group extensions of the Standard Model represent one of the most minimal approaches to solve some of the most urgent particle physics questions and provide a rich phenomenology in various experimental searches. In this work, we focus on baryophilic vector mediator models in the MeV-to-GeV mass range and, in particular, present, for the first time, gauge vector field decays into almost arbitrary hadronic final states. Using only very little theoretical approximations, we rigorously follow th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 92 publications
(138 reference statements)
0
1
0
Order By: Relevance
“…Instead, different approaches are required to obtain a realistic description of the particles lifetimes, decay branching fractions and decay kinematics. For example, it has been shown that fits to low energy scattering data can be used to predict the dark photon decay widths into various hadronic channels [1259]. An implementation of these results in common MC tools would be a valuable input for related experimental efforts.…”
Section: Tools For Bsmmentioning
confidence: 99%
“…Instead, different approaches are required to obtain a realistic description of the particles lifetimes, decay branching fractions and decay kinematics. For example, it has been shown that fits to low energy scattering data can be used to predict the dark photon decay widths into various hadronic channels [1259]. An implementation of these results in common MC tools would be a valuable input for related experimental efforts.…”
Section: Tools For Bsmmentioning
confidence: 99%